“Makam” Nasi: Language Interference of a Japanese Young Learner in Indonesia - Kadek Eva Krishna Adnyani; Ni Wayan Nilam Puspawati; Ni Komang Arie Suwastini (Jurnal Pendidikan dan Pengajaran, 2021)
In acquiring the second language, children will use their first language knowledge as a base in their attempt of using a new language. This phenomenon is called language interference. This study aimed at identifying specific instances of language interference conducted by a bilingual child during her study in an international school. The subject was a 5-year-old Japanese child who was acquiring Indonesian as her second language. This study was a case study using descriptive qualitative research method. Data collection was done through observation, interview and note taking. Furthermore, the data in the form of utterances in Indonesian interfered by Japanese were analyzed descriptively. The results showed that the most common type of language interference occurred was phonological interference (16 examples), followed by lexical error (4 words) and grammatical error (5 sentences). In short, in this case, Japanese phonological interference with Indonesian pronunciation occurred more frequently than lexical error and grammatical error.